PERANCANGAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU DAN BARANG JADI PADA PT. SMU - Rahma, Hanum Yustisia; Abdussalaam, Falaah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
PT. SMU is a manufacturing business company that produces foods such as cheese. The research conducted found problems with the manual process that is still used to record the inventory of raw materials and finished goods so that the recording process is less effective. The purpose of this design is to create a computerized system to record the inventory of raw materials and finished goods at PT. High school quickly and precisely. The research technique uses qualitative methodology with tools to collect data through observation, interviews and literature review. The waterfall approach is used to develop the software and the stages involved including Flow map, Context Diagram, Data Flow Diagram and Entity Relationship Diagram are then implemented using Microsoft Visual Studio 2012 using Microsoft Access 2019 as a database. The results of the research conducted that with the existence of an accounting information system for raw material and finished goods inventory at PT. SMU can ease the work of employees in inputting raw material and finished goods inventory quickly and more effectively.